SOME CONTEMPORARY ISSUES OF THE CONCEPT OF DAMAGE - Melqumyan, Miqayel (State and Law, 2022)
The institution of compensation is of vital importance in the field of human rights protection. Damage is the basic concept of the institution of compensation, since, on the one hand, it is an indispensable condition for the emergence of these legal relations, and on the other hand, it allows you to differentiate legal relations from other legal relations aimed at restoring the rights of the impaired party.Damage is usually defined as restriction of property or personal benefit. Accordingly, two types of damage are differentiated - material and non-material, which are equally subject to compensation by the entities responsible for its compensation.Summarizing the conclusions made in the work, it can be stated that any violation of a subjective right causes damage, each right is subject to separate protection, and the damage caused by the violation of the right, including mental anguish, is subject to compensation.
Keywords: damage; concept; material; moral, type; impaired party; compensation; legal relation